Exercising in the urban center: Inflammatory and cardiovascular effects of prolonged exercise under air pollution. (September 2020) - Pasqua, Leonardo A.; Damasceno, Mayara V.; Cruz, Ramon; Matsuda, Monique; Martins, Marco A.G.; Marquezini, Mônica V.; Lima-Silva, Adriano E.; Saldiva, Paulo H.N.; Bertuzzi, Romulo
Abstract: The aim of this study was to investigate, in a well-controlled experimental environment, whether air pollution from an urban center would affect inflammatory and cardiorespiratory responses during prolonged moderate exercise (i.e., 90 min). Ten healthy men performed two experimental trials under filtered and polluted air, inside an environmental chamber located in Sao Paulo downtown, Brazil. Blood samples were obtained at rest, 30, 60, and 90 min of the exercise to determine the serum cytokines concentration, while arterial pressure was recorded immediately after the exercise. The serum cytokines were not altered until 60 min of exercise for both conditions (P > 0.05). Otherwise, at 90 min of exercise, the IL-6 (P = 0.047) and vascular endothelial growth factor (VEGF) (P = 0.026) were significantly higher and IL-10 tended to decrease (P = 0.061) in polluted air condition compared to filtered air condition. In addition, both systolic (P = 0.031) and diastolic (P = 0.009) arterial pressure were higher in polluted air condition than filtered air condition. These findings demonstrate that the exercise of longer duration (i.e., 90 min), but not of shorter duration (i.e., <60 min), performed in vehicular air pollution condition results in pronounced pro-inflammatory and increased arterial pressure responses. Highlights: Effects of air pollution during exercise seem to be dependent on exercise duration. Air pollution during long duration exercise might increase post arterial pressure. Systemic inflammation occurs after long exercise under air pollution exposure. Distance should be considered in active transportation under air pollution exposure.